Talent Management and Public Service Optimization (Literature Study) - Shinta Surya Idrus; Maudhy Satyadharma; Alfasari Ode Rusli; Adjaran Sirait; Rezki Fidmasari; Hado (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
This research is a literature study that aims to analyse the role of talent management in supporting the optimisation of public services. Talent management is seen as a strategic approach to ensure the availability of quality human resources in the bureaucracy, through the process of identifying, developing, and retaining high-potential individuals. In this study, literature was added through a systematic search process using scientific databases such as Google Scholar and ResearchGate, with the keywords "talent management in the public sector," "bureaucratic reform," and "public service performance." The selected literature includes indexed international journals and e-books published from 2020 to 2025 to ensure relevance and topicality. This study highlights that the implementation of effective talent management can improve the performance of public organizations, encourage innovation, and strengthen the accountability and responsiveness of services to the public. However, the success of its implementation is greatly influenced by the commitment of the leadership, a competency-based management system, and a supportive organizational culture. This study also identifies challenges in the implementation of talent management in the public sector, such as limited regulations, political intervention, and a lack of integration with strategic planning. Thus, talent management is a vital foundation in bureaucratic reform to create more professional, effective, and community-oriented public services.